Beneficial Probiotics with New Cancer Therapies for Improved Treatment of Hepatocellular Carcinoma - Moeka Nakashima; Akari Fukumoto; Satoru Matsuda (Diseases)
Hepatocellular carcinoma (HCC) is a malignant form of primary liver cancer. Intricate networks linked to the host immune system may be associated with the pathogenesis of HCC. A huge amount of interdisciplinary medical information for the treatment of HCC has been accumulated over recent years. For example, advances in new immunotherapy have improved the results of treatment for HCC. This approach can be advantageously combined with standard conventional treatments such as surgical resection to improve the therapeutic effect. However, several toxic effects of treatments may pose a significant threat to human health. Now, a shift in mindset is important for achieving superior cancer therapy, where probiotic therapy may be considered, at least within the bounds of safety. The interplay between the gut microbiota and immune system could affect the efficacy of several anticancer treatments, including of immune checkpoint therapy via the alteration of Th17 cell function against various malignant tumors. Here, some recent anticancer techniques are discussed, whereby the growth of HCC may be effectively and safely repressed by probiotic therapy.